Crystal Growth and Chirality Technologies and Applications - Marzouki, Riadh; Akitsu, Takashiro (IntechOpen, 2023)
Crystal growth is the process of arranging atoms, ions, molecules, or molecular assemblies into regular three-dimensional periodic lattices. There are different synthesis and crystal growth methods depending on the material available, such as evaporative synthesis, hydrothermal method, and solid-state reaction. Crystal growth technology has various applications, including in the production of semiconductor devices, solar cells, and optical components. In this book, we deal with some crystalline materials synthesized by different methods, their crystal growth in relation to their physical properties or biological activities, and their applications, in particular in biology, medicine, and semiconductors.